STUDI PENERAPAN PRINSIP KONSUMSI ISLAM (KASUS MASYARAKAT PESISIR DI DESA KAWITE WITE KECAMATAN KABAWO KABUPATEN MUNA) - Aldi, Aldi; Harafah, LM; Gamsir, Gamsir (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
This study aims to determine the application of consumption principles according to Islamic law in Kawite-Wite Village, Kabawo District, Muna Regency. The analysis used in this research is descriptive qualitative. Determination of respondents in this study was determined by using the simple random sampling method with the number of respondents 76 people. Data collection methods used in this study are observation, questionnaires, and documentation. The results showed that by looking at the parcentage value ofeach sub-variable, the consumption principle of coastal communities was in accordance with Islamic law, although there were still people who carried out food consumption activities that werw not in accordance with the principles of Islamic law. This is because most of them consume cigarettes and alcoholic bevarages (Alcohol).